2008
DOI: 10.1017/s0025315408001938
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of marine yeasts with high protein content and evaluation of their nutritive compositions

Abstract: A total of 327 yeast strains from seawater, sediments, mud of salterns, guts of the marine fish and marine algae were obtained. After crude protein of the yeasts was estimated by the method of Kjehldahl, we found that eight strains of the marine yeasts grown in the medium with 20 g l−1 glucose contained more than 30.4 g protein per 100 g of cell dry weight. The results of routine identification and molecular methods show that they belong to Metschnikowa reukaui, Cryptococcus aureus, Aureobasidium pullulan, Yar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…pullulans has not been explored for its use as a source of SCP, but fungi proteins have more advantages than those obtained from bacteria and algae [89]. Work from Chi et al [90] showed that A. pullulans isolates had high levels of nucleic acid components and essential amino acids. Such properties could be helpful in wine fermentation if these components can be used for feeding the alcohol-and aroma-producing yeasts.…”
Section: Single-cell Proteinmentioning
confidence: 99%
“…pullulans has not been explored for its use as a source of SCP, but fungi proteins have more advantages than those obtained from bacteria and algae [89]. Work from Chi et al [90] showed that A. pullulans isolates had high levels of nucleic acid components and essential amino acids. Such properties could be helpful in wine fermentation if these components can be used for feeding the alcohol-and aroma-producing yeasts.…”
Section: Single-cell Proteinmentioning
confidence: 99%
“…When the state of the herring meal and the processing wastes silage in the 30th day are compared in terms of amino acid composition and the content of essential amino acids, valine, methionine and phenylalaline were found to be much lower when compared to those in the fish meal, threonine and lysine were high, while histidine, isoleucine and leucine were found to be similar (Table 3). As the amino acid index in the study was above 0.95 for both of the silages (Table 1 and 2), it was concluded that the silages contain high quality protein [25]. It is believed that the silage will be a raw material with high quality protein that could be an alternative to the fish meal when the amount of protein deficit of the silage is supplemented by enrichers.…”
Section: Resultsmentioning
confidence: 80%
“…Samples were placed in the flask of the rotary evaporator, and after the water bath was adjusted to 65°C, the hydrochloric acid was evaporated. Then, the remaining samples were taken up in dilution solution with citrate-sodium citrate buffer (0.1 M, pH 2.2) and became ready for amino acid analysis (Chi et al, 2008;Srivastava, Hamre, Stoss, Chakrabarti, & Tonheim, 2006).…”
Section: Amino Acid Analysesmentioning
confidence: 99%